Emergence of a Novel Lineage and Wide Spread of a blaCTX-M-15/IncHI2/ST1 Plasmid among Nosocomial Enterobacter in Guadeloupe - Matthieu Pot; Yann Reynaud; David Couvin; Alexis Dereeper; Séverine Ferdinand; Sylvaine Bastian; Tania Foucan; Jean-David Pommier; Marc Valette; Antoine Talarmin; Stéphanie Guyomard-Rabenirina; Sébastien Breurec (MDPI AG, 2022)
Between April 2018 and August 2019, a total of 135 strains of Enterobacter cloacae complex (ECC) were randomly collected at the University Hospital Center of Guadeloupe to investigate the structure and diversity of the local bacterial population. These nosocomial isolates were initially identified genetically by the hsp60 typing method, which revealed the clinical relevance of E. xiangfangensis (n = 69). Overall, 57/94 of the third cephalosporin-resistant strains were characterized as extended-spectrum-β-lactamase (ESBL) producers, and their whole-genome was sequenced using Illumina technology to determine the clonal relatedness and diffusion of resistance genes. We found limited genetic diversity among sequence types (STs). ST114 (n = 13), ST1503 (n = 9), ST53 (n = 5) and ST113 (n = 4), which belong to three different Enterobacter species, were the most prevalent among the 57 ESBL producers. The blaCTXM-15 gene was the most prevalent ESBL determinant (56/57) and was in most cases associated with IncHI2/ST1 plasmid replicon carriage (36/57). To fully characterize this predominant blaCTXM-15/IncHI2/ST1 plasmid, four isolates from different lineages were also sequenced using Oxford Nanopore sequencing technology to generate long-reads. Hybrid sequence analyses confirmed the circulation of a well-conserved plasmid among ECC members. In addition, the novel ST1503 and its associated species (ECC taxon 4) were analyzed, in view of its high prevalence in nosocomial infections. These genetic observations confirmed the overall incidence of nosocomial ESBL Enterobacteriaceae infections acquired in this hospital during the study period, which was clearly higher in Guadeloupe (1.59/1000 hospitalization days) than in mainland France (0.52/1,000 hospitalization days). This project revealed issues and future challenges for the management and surveillance of nosocomial and multidrug-resistant Enterobacter in the Caribbean.